The Federal Income Tax and Reform of College Athletics: A Response to Professor Colombo and an Independent Critique - Lyons, William H.; Potuto, Josephine R. (Journal of Intercollegiate Sport, 2009)
Large athletics programs bring a lot of attention to themselves and the universities of which they are a part. Once, that attention came only from success on the field or court. Now it also comes from how much money these programs spend, and on what, and its source. Calls to use the federal tax code to rein in athletics spending are, we believe, ill-advised. The IRS has limited resources and a lot to do. Its staff members know tax law, not the ins and outs of college athletics. Because universities are adept at “zeroing out” revenues and expenses, it is unlikely that new tax rules and added IRS oversight would do much to curtail spending. They could, however, impose significant compliance costs on universities. The result could be the worst of all worlds: considerable expense on universities to comply; little or no spending reform achieved; and an IRS diverted from core responsibilities.